Iron doped cobalt phosphide ultrathin nanosheets on nickel foam for overall water splitting. Issue 36 (30th August 2019) - Li, Ying; Li, Fumin; Zhao, Yue; Li, Shu-Ni; Zeng, Jing-Hui; Yao, Hong-Chang; Chen, Yu
Abstract : Iron doped cobalt phosphide ultrathin nanosheets on nickel foam are used as a bifunctional electrocatalyst for overall water splitting in alkaline electrolyte. Abstract : The development of active and durable non-precious metal based bifunctional electrocatalysts for overall water splitting is an urgent yet challenging task. In this work, we have successfully achieved iron doped cobalt phosphide ultrathin nanosheets (Fe-CoP UNSs) with a 2.3 nm thickness on a nickel foam (NF) substrate (termed Fe-CoP UNSs/NF) by high-temperature phosphidation treatment using atomically thick Fe doped cobalt oxide nanosheets as the reaction precursor. Because of the large surface area, sufficient edge active sites, synergistic effect between heteroatoms, high conductivity of the NF substrate, and porous structure of the NF substrate, Fe-CoP UNSs/NF displays outstanding electrocatalytic performance for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in a 1 M KOH electrolyte, such as overpotentials of 67 and 166 mV at current densities of 10 mA cm −2 and 50 mA cm −2, respectively. More importantly, Fe-CoP UNSs/NF can serve as a bifunctional electrocatalyst for overall water splitting, achieving a 10 mA cm −2 current density at a voltage of only 1.46 V in an alkaline electrolyte.